2004
DOI: 10.1111/j.1365-2036.2004.02284.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability in patients with irritable bowel syndrome after a waterborne outbreak of acute gastroenteritis in Walkerton, Ontario

Abstract: SUMMARYBackground: Post-infectious irritable bowel syndrome is a common clinical phenomenon of uncertain aetiology. Aim: To test the association between intestinal permeability and irritable bowel syndrome symptoms 2 years after a large waterborne outbreak of bacterial gastroenteritis. Methods: Consecutive adults with Rome I irritable bowel syndrome and controls without irritable bowel syndrome attending a community clinic were enrolled. Intestinal permeability was measured as the ratio of fractional urinary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
193
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(203 citation statements)
references
References 24 publications
9
193
0
Order By: Relevance
“…36,37 Whether similar mechanisms are implicated in the increased permeability during the developmental period at weaning need to be further investigated. Intestinal barrier disruption has been described to occur in IBS patients, [38][39][40][41] although the link between early adverse life events and increased intestinal permeability needs to be evaluated based on the present experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Whether similar mechanisms are implicated in the increased permeability during the developmental period at weaning need to be further investigated. Intestinal barrier disruption has been described to occur in IBS patients, [38][39][40][41] although the link between early adverse life events and increased intestinal permeability needs to be evaluated based on the present experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal permeability, determined by the ratio of lactulose to manitol excreted in urine, was significantly higher in PI-IBS patients compared to controls (22) . Several authors have suggested that increased intestinal permeability may allow the access of bacterial and luminal antigens to the submucosa, which could perpetuate chronic inflammation and disrupt enteric sensation and motility, that have been implicated in the pathogenesis of IBS (7,14,17,24) .…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal permeability is increased in post-infectious IBS (PI-IBS) patients [85,86]. The changes associated with such increased permeability must be preceded by a lack of recovery from the disruption of the TJ that occurred during acute infection.…”
Section: Irritable Bowel Syndrome (Ibs)mentioning
confidence: 99%